Pengaruh Literasi Keuangan dan Pendapatan terhadap Keputusan Investasi pada Mahasiswa Investor Aktif Fakultas Ekonomi dan Bisnis Universitas Teknologi Sumbawa - artianingsih, Okpita (CV. Kalimasada Group, 2024)
This study aims to determine the effect of financial literacy and income on investment decisions in active investor students, Faculty of Economics and Business, Sumbawa University of Technology. The population in this study was 114 students who had been enrolled at KSPM Sumbawa University of Technology. The sample of this study amounted to 53 respondents. The method used is quantitative research using an associative approach. The data sources used are primary and secondary data through the distribution of questionnaires. The analysis techniques used are data quality tests, descriptive analysis tests, classical assumption tests, multiple linear regression tests, and hypothesis tests with the help of SPSS 25.0. The results of the study show that (1) financial literacy has a significant effect on investment decisions, (2) income does not affect investment decisions, (3) financial literacy and income have a simultaneous and significant effect on investment decisions.